Factors Influencing the Cost for Effective Heritage Building Maintenance Programme: Case Study in Ipoh, Perak - SYED MOHAMAD, SYED BURHANUDDIN HILMI; Muhamad Syukry Mohd Radzuan,; Zainal Abidin Akasah, (Recent Trends in Civil Engineering and Built Environment, 2020)
The abandoned buildings continue to be used and given new breath in terms of appearance, functionality and historical value. Maintenance costs are the most critical factor in order to conduct the best approach in heritage building maintenance. Shortage of annual maintenance budget will reduce the building services capacity and system effectiveness. The objectives of this study are to identify the factors influencing the cost of effective program maintenance for building heritage, to determine the significant factors influencing the cost of effective program maintenance for building heritage, and to suggest the best approaches in preparing effective maintenance programs for heritage buildings. The building becomes a subject for this case study is Dewan Bandaraya Ipoh. The method used in this study is conducting by using a structured interviews. The selected respondents were been asking a question with the help of a Likert Scale to ease them in answering the questions. Most of respondents are those who were involved directly with heritage building maintenance. The factors of building age and existing building condition become the most influencing factors for the cost of each effective maintenance program for Dewan Bandaraya Ipoh buildings in Ipoh, Perak. In conclusion, one of the work flow diagram have been suggested and modified as the best approach of an effective maintenance programme for a heritage building. The workflow eliminates unnecessary decisions, and it could reduce the time taken to decide on a maintenance programme.